EXPECTATIONS AND PERFORMANCE OF MARINE ENGINEERING STUDENTS - Bilan, Engr. Evelyn A. (Proceeding of the International Conference on Family Business and Entrepreneurship, 2024)
The study examined the expectations and performance of the marine engineering students for school year 2022 – 2023. Descriptive correlational method with researcher constructed survey questionnaire were used in the research. Part 1 of the survey dealt on questions respondents' sociodemographic profile, and part 2 had questions about their expectations composed of physical environment, facilities, instruction, promotion of the school and performance. The respondents were between 18 - 19 years old, second year and with monthly income of 15,000. Classroom have enough space for test and note taking, spacious to accommodate large audiences and lighting is appropriate for lectures and pleasant for audio/visual presentation often. In a similar vein, factors related to seat placement and selection were frequently evaluated by row, front, middle, and back of the room, center versus perimeter of the room, and mid-room versus sides of the room in order to ascertain which area of the room and environmental factor encouraged higher ratings. Regarding facilities, lighting in the classrooms, projectors, writing supplies for blackboards and whiteboards are available, school parking lot is large enough, benches are in good condition but some of the chairs need repair. Additionally, it has well-kept facilities, kind teachers who communicate well, creative teaching methods, and knowledgeable who frequently provide succinct explanations and vivid examples. It is inferred, the instructors' subject-matter expertise, the classroom's suitable balance of theoretical and practical experience, the value of the lessons learned in class for advancing one's career, their level of satisfaction with the course curriculum, and their grade were the main factors motivating students to recommend the school to their friends and colleagues. Findings highlight 455 students garnered a grade of 1.75 considered superior and those with a grade of 1.5 were lesser compared to those with a grade of 2.50.Students who received a grade of 1.75, was much higher than those students with a grade of 1.5 and several did not perform well than those with a grade of 2.50. Students with average grades were even lower than those with above-average ratings and the number of students with a 2.0 grade fell after the grade increased from 1.5 to 1.0.